Benefits And Risks Of Marketing Patchouli Oil In Morengke Village, Matata Usu District, Bombana District - Ismawati, Ismawati; Weka Gusmiarty Abdullah; Hidrawati, Hidrawati (International journal of technology and education research, 2023)
This study aims to 1) know the profit of marketing Patchouli oil in Mata Usu District, Bombana Regency, and 2) todescribe the risks of n ilam oil marketing in Mata Usu District, Bombana Regency. This research was carried out in Morengke Village, Mata Usu District, Bombana Regency. The number of samples in this study consisted of 16 patchouli distillery business industry owners, 4 collecting traders, and 2 marketing institutions. The determination of samples is carried out by the census method, which is to take the entire population to be used as a research sample while teknik determination of samples in collecting merchants or marketing institutions is carried out with snowball sampling techniques because the number is not yet known how many.The data analysis used is marketing margin analysis and risk analysis. The results showed that 1) the profit obtained by each patchouli oil marketing institution in Morengke Village was a trader (a) collector of Rp32.739.040 per month; (b) wholesalers amounting to Rp80.023.068 per month, 2) type of risiko in patchouli oil marketing in Morengke Village, Masa Usu District, Bombana Regency, among others, the quality of patchouli oil is low at the purchase stage caused by high acid and pH levels are in the medium risk category, the risk event in patchouli oil discoloration is at the storage stage due to too long storage, low temperature conditions, the use of patchouli oil storage containers are not suitable to be in the medium risk category, the occurrence of erratic price risk is at the storage stage caused by poor oil quality, traders accommodate patchouli oil are in the high risk category, and 3) upaya company in overcoming the risks faced on the risks Patchouli oil sales are carried out by strengthening marketing management and discussing with competitors a good marketing process without having to commit sales fraud by analyzing market competition and competitor performance in order to create a competitive market properly